Developing computational thinking in early ages: a review of the code.org Platform - Barradas, Rolando (2020)
This article reports a pedagogical experience developed within the scope of a Ph.D. program in Electrical and Computer Engineering with application to Education. Starting with a contextualization on the evolution of computers and Computational Thinking, the article describes the platform used in this study - code.org -, highlighting the strengths that captivate the students. In the Case Study topic, we describe the study carried out, starting with a description of the students involved, followed by a description of the process and the analysis of the results, ending with the evaluation process performed by the students. The article ends concluding that code.org is a valid option to develop computational thinking at early-ages.